Introducing EMP-Pathfinder: modelling the simultaneous formation and evolution of stellar clusters in their host galaxies - Reina-Campos, Marta; Keller, Benjamin W.; Kruijssen, Diederik; Gensior, Jindra; Trujillo-Gomez, Sebastian; Jeffreson, Sarah M R; Pfeffer, Joel L; Sills, Alison (Monthly notices of the Royal Astronomical Society, 2022)
The formation and evolution of stellar clusters is intimately linked to that of their host galaxies. To study this connection, we present the emp-Pathfindersuite of cosmological zoom-in Milky Way-mass simulations. These simulations contain a subgrid description for stellar cluster formation and evolution, allowing us to study the simultaneous formation and evolution of stellar clusters alongside their host galaxies across cosmic time. As a key ingredient in these simulations, we include the physics of the multiphase nature of the interstellar medium (ISM), which enables studies of how the presence of a cold, dense ISM affects star cluster formation and evolution. We consider two different star formation prescriptions: a constant star formation efficiency per free-fall time, as well as an environmentally dependent, turbulence-based prescription.
Gesehen am 03.01.2023